Toxicity, antifeedant, egg hatchability and adult emergence effect of Piper nigrum L. and Jatropha curcas L. extracts against rice moth, Corcyra cephalonica (Stainton) - Khani, Mousa; Muhamad Awang, Rita; Omar, Dzolkhifli; Rahmani, Mawardi (Academic Journals, 2013)
Petroleum ether extract of black pepper, Piper nigrum and physic nut, Jatropha curcaswere shown to have insecticidal efficacies against rice moth, Corcyra cephalonica(Stainton). The C. cephalonica 3rd instar larvae were shown to have similarities susceptibility to petroleum ether extract of Piper nigrum and J. curcas with LC50 values of 12.52 and 13.22 µL/ml, respectively. In a bioassay using no-choice tests, the parameters used to evaluate antifeedant activity were relative growth rate (RGR), relative consumption rate (RCR), efficiency on conversion of ingested food (ECI) and grain protection or feeding deterrence indices (FDI). Both extracts showed high bioactivity at all doses against C. cephalonica larvae and antifeedant action was increased with increasing plant extract concentrations. The petroleum ether extract of P. nigrum and J. curcas showed strong inhibition on egg hatchabilities and adult emergence of C. cephalonica at the lowest concentration. Based on the results of this study, petroleum ether extracts of P. nigrum andJ. curcas could be used in IPM program for rice moth.